2005
DOI: 10.1536/ihj.46.783
|View full text |Cite
|
Sign up to set email alerts
|

<b>Simultaneous Carotid Endarterectomy and Coronary Revascularization is Safe Using Either On-Pump or Off-Pump Technique</b>

Abstract: SUMMARYThe appropriate surgical strategy for patients with combined carotid and coronary artery disease remains controversial. We retrospectively compared our surgical results for 2 types of approaches in this disorder.The records of 76 patients consecutively operated on for carotid and coronary artery disease between August 1993 and October 2004 were reviewed. There were 18 males (66.6%) and 9 females (33.3%) in group I. Group II consisted of 35 males (71.4%) and 14 females (28.5%). The patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In our clinic, off-pump CABG has been in practice since 1993, and is mainly preferred for single or double vessel revascularization. A previous study by Eren et al [25] from our center reported no stroke and 3.7% mortality for patients who had CEA and simultaneous off-pump CABG. In the literature, reported rate of mortality is between 0-4.5% and rate of stroke is between 0-3.1% for combined CEA and off-pump CABG [16,21-24] .…”
Section: Discussionmentioning
confidence: 75%
“…In our clinic, off-pump CABG has been in practice since 1993, and is mainly preferred for single or double vessel revascularization. A previous study by Eren et al [25] from our center reported no stroke and 3.7% mortality for patients who had CEA and simultaneous off-pump CABG. In the literature, reported rate of mortality is between 0-4.5% and rate of stroke is between 0-3.1% for combined CEA and off-pump CABG [16,21-24] .…”
Section: Discussionmentioning
confidence: 75%
“…Totally 41,901 patients undergoing simultaneous or staged carotid and coronary procedures were collected from 53 reports (Evagelopoulos et al 2000;Snider et al 2000;Minami et al 2000;Gaudino et al 2001;Hamulu et al 2001;Youssuf et al 2001;Estes et al 2001;Farooq et al 2001;Bonacchi et al 2002;Bonardelli et al 2002;Antunes et al 2002;Zacharias et al 2002;Meharwal et al 2002;Roddy et al 2002;Char et al 2002;Beauford et al 2003;Brown et al 2003;Vitali et al 2003;Ricotta et al 2003;Srimahachota et al 2004;Mishra et al 2004;Ricotta et al 2005;Ziada et al 2005;Cinar et al 2005;Eren et al 2005;Chiappini et al 2005;Akins et al 2005;Nwakanma et al 2006;Inciura and Benetis 2006;Kolh et al 2006;Byrne et al 2006;Cywinski et al 2006;Kovacic et al 2006;Mendiz et al 2006;Randall et al 2006;Chiariello et al 2006;Hertzer and Mascha 2006;Madi-Jebara et al 2006;Kougias et al 2007;Dubinsky and Lai 2007;…”
Section: Resultsmentioning
confidence: 99%
“…However, even large cohort reports concluded that equally good results for cardiac and neurological events can be reproduced using either cardiopulmonary bypass or off-pump techniques for coronary artery surgery, and conventional carotid endarterectomy or CAS for carotid artery surgery. [24][25][26][27] At present, protein S100B, neuron-specifi c enolase (NSE), myelin basic protein, and glial fi brillary acidic protein are being evaluated as marker proteins in cerebrospinal fl uid and/or blood for detection of brain injury in patients with stroke or brain injury. 28 H-FABP has been used as a biochemical plasma marker for myocardial infarction, neurological disorders, or brain injury.…”
Section: Discussionmentioning
confidence: 99%